FINANCIAL INSTRUMENTS ON COMPANY VALUE IN COMPANIES LISTED IN JAKARTA ISLAMIC INDEX (JII) - Solichah; Dwi Dewianawati; Erry Setiawan; Agus Sunaryo (International Journal of Social Science, 2021)
Based on the background and problem formulation, the objective is to test, analyze and prove that asset structure, capital structure, macroeconomic, financial risk management, and profitability performance affect the firm value of companies listed in JII. Researchers determine the type of quantitative research. Descriptive data analysis technique, is a technique used to analyze data by describing or describing the data that has been collected. The data used by researchers is secondary data, the data in this study were obtained from the IDX website (Indonesian Stock Exchange). So the population used in this study found 16 companies. Jakarta Islamic Index. The results of the study 1) there is no influence of asset structure on financial risk management, 2) there is an influence of asset structure on profitability performance, 3) there is an influence of asset structure on the value of the firm, 4) there is an influence of capital structure on financial risk management, 5) there is the effect of capital structure on profitability performance, 6) there is no effect of capital structure on the value of the firm, 7) there is a macroeconomic influence on financial risk management, 8) there is a macroeconomic effect on profitability performance, 9) there is a macroeconomic influence on the value of the firm, 10) there is the influence of financial risk management on the profitability performance, 11) there is the influence of financial risk management on the value of the firm, 12) there is the influence of profitability performance on the value of the firm.